Maedi Visna virus infection and TMEM154 genotypes in Valle del Belìce sheep breed - Silvia Riggio; Rosalia Di Gerlando; Salvatore Mastrangelo; Ilaria Rizzuto; Marco Tolone; Maria Teresa Sardina (Italian Journal of Animal Science)
Maedi Visna (MV) is a viral infection in sheep caused by Lentivirus and characterised by a long incubation period, slow progression, weight loss and eventually death. TMEM154 was reported in the ovine as major candidate gene associated with host susceptibility/resistance. The aim of this study was to verify the prevalence of MV infection within Sicilian herds of Valle del Belìce breed using an ELISA serological test and to estimate the frequencies of the resistant/susceptible genotypes to the TMEM154 gene. Finally, we investigated the association between TMEM154 E/K genotype and MV infectious status. A total of 1,083 animals from different flocks were tested. The ELISA method showed 15.33% (n = 166) of infected individuals. Analyses of the sequences showed the presence of both K and E alleles with frequencies of 0.151 and 0.849, respectively. On the total individuals, only 23 carried KK genotype while 280 were heterozigous EK, and 780 homozygous EE. The locus was in Hardy-Weinberg equilibrium in the breed (p-value <0.05) and observed and expected heterozygosity values were 0.258 and 0.256, respectively. Moreover, a significant association (p-value < 0.001) between TMEM154 genotypes and seroprevalence status (positive vs. negative) was found. This study allowed us to know the prevalence of MV infection in Sicilian flocks of Valle del Belìce breed and could be helpful in establishing selection programs aimed at controlling and eradicating this virus.